Label-free quantitative proteomic analysis of ethanamizuril-resistant versus -sensitive strains of Eimeria tenella - Cheng, Peipei; Wang, Chunmei; Zhang, Lifang; Fei, Chenzhong; Liu, Yingchun; Wang, Mi; Zhang, Keyu; Wang, Xiaoyang; Gu, Feng; Xue, Feiqun (Parasites & vectors, 2022)
Avian coccidiosis is an important parasitic disease that has serious adverse effects on the global poultry industry. The extensive use of anticoccidial drugs has resulted in an increase in drug resistance. Ethanamizuril (EZL) is a novel triazine with high anticoccidial activity. We compared oocyst production and sporulation between EZL-sensitive (S) and EZL-resistant Eimeria tenella strains (R10 and R200) and used label-free quantitative proteomics to identify differentially expressed proteins (DEPs) between these strains. We generated two EZL-resistant E. tenella strains: strain R10, which was induced using a constant dose of 10 mg EZL/kg poultry feed, and strain R200, which was generated by gradually increasing the EZL dosage to 200 mg EZL/kg poultry feed. With an increase in resistance, the total oocyst output decreased, but the percentage of sporulation did not change significantly. We identified a total of 7511 peptides and 1282 proteins, and found 152 DEPs in the R10 strain versus the S strain, 426 DEPs in the R200 strain versus the S strain and 494 DEPs in the R200 strain versus the R10 strain. When compared with the S strain, 86 DEPs were found to have consistent trends in both resistant strains. The DEPs were primarily involved in ATP and GTP binding, invasion, and membrane components. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses of the DEPs suggested that they are involved in transcription and translation processes. Protein-protein interaction network analysis of the 86 DEPs showed that 10 proteins were hubs in the functional interaction network ([greater than or equal to] 8 edges) and five of them were ribosomal proteins. The results of the present study indicate that the resistance mechanisms of E. tenella against EZL might be related to the transcriptional and translational processes, especially in the factors that inhibit the growth of parasites. The DEPs found in this study provide new insights into the resistance mechanisms of E. tenella against EZL. Further research on these potential targets holds promise for new chemotherapeutic approaches for controlling E. tenella infections.